PENGARUH MEDAN LISTRIK TERHADAP ORIENTASI MOLEKUL DISPERSE RED-19 TERDEPOSISI DI ATAS SUBSTRAT SILANE DENGAN METODE PHYSICAL VAPOR DEPOSITION - Deitje Sumolang; Donny Royke Wenas; Alfrits Komansilan (Jurnal FisTa : Fisika dan Terapannya, 2020)
Molecular Disperse Red 19 (DR-19) is known as a potential material for photonic device applications such as optical switching and optical data storage. For the application of this photonic device, a good quality film is needed, which has a flat surface, homogeneous thickness, optical stability, and good optical properties.This study aims to examine the effect of the silane substrate surface and the external electric field of 3.3 MV / m in regulating the molecular orientation of the DR-19 film on the silane substrate surface.The fabrication method used is the PVD (Physical Vapor Deposition) method assisted by an external electric field. The film was made on the surface of the silane substrate with the deposition of DR-19 molecules in a variety of external electric fields, namely no electric field (zero field) and the electric field E = 3.3 MV / m. The films were analyzed and characterized using X-ray diffraction spectroscopy (XRD). The results of the X-ray diffraction measurement analysis show that the DR-19 molecules are stacking perpendicular to the surface of the silane substrate, which shows an indication of the strong surfactant effect of the substrate from the hydrogen bonding of the DR-19 molecule with silane substrate. The results of spectroscopic measurements show that with the increase in the external electric field, there is an increase in the effect of aggregation of molecules arranged in an orderly manner perpendicular to the surface of the silane substrate.